Transcutaneous pacing: a life saviour - Mishra, Roly; Thakkar, Parna; Mehta, Hemant (International Journal of Research in Medical Sciences, 2020)
Doukky Rand colleagues acknowledged that Transcutaneous Cardiac Pacing is a temporary method of pacing which may be indicated in patients with symptoms of severe or hemodynamically unstable bradyarrhythmias. It is found to be extremely helpful in patients with reversible or transient conditions, such as digoxin toxicity and in atrioventricular block in the case of inferior wall myocardial infarction, or when transvenous pacing is not available or there are high chances of complications. Widened QRS complex indicates successful attempt followed by a distinct ST segment and broad T wave. The hemodynamic response to pacing is to be confirmed by the assessment of patient’s arterial pulse waveforms. Trancutaneous pacing is a boon to manage and treat intra op dangerous bradycardia.